Women's confidence in their body’s ability to give birth: Its antecedents and effects on the birth experience and postpartum adjustment - Hadjigeorgiou, Eleni (My University, 2026)
Εvaluation of the research proposal submitted to The Israel Science Foundation, on the Personal Research Grants.